The unified body of Christ as Biblical metaphor for being church - Lourens Schoeman (Acta Theologica)
The church, as faith community, is described with the metaphor of one body, with all members interlinked to each other, helping each other, praying for each other, serving each other. The reality is that this church, like the secular community (locally, provincially, nationally, throughout Africa and globally) is divided into class, wealth and health categories. Is this “world-like” fragmented existence of the church depriving her of her unique role as source of hope in a given community? Is she loosing face in the world due to this “world-like” fragmented way of living? Can she better meet the social challenges, related to poverty and HIV, if, as alternative community, rich and poor were indeed living as one body? How would she then define and respond to poverty and HIV infection?